Influence of Solvent and Electrical Voltage on Cathode Plasma Electrolytic Deposition of Al2O3 Antioxidation Coatings on Ti-45Al-8.5Nb Alloys - Xu Yang; Zhipeng Jiang; Xianfei Ding; Guojian Hao; Yongfeng Liang; Junpin Lin (Metals, 2018)
Al2O3 coatings were prepared on Ti-45Al-8.5Nb alloys via cathodic plasma electrolysis deposition (CPED) in both 1.2 M Al(NO3)3 aqueous and ethanolic solutions. Different voltages were also applied during the deposition process to optimize coating properties. Coatings deposited in both solutions mainly consisted of γ-Al2O3, with some Al(OH)3 found in coatings prepared in aqueous solution. Coatings prepared in ethanol solution exhibited better oxidation resistance at 900 °C as well as better substrate adhesion, which was mainly due to smaller crater sizes on coating surfaces. The deposition process was discussed in detail and the reason for the smaller craters examined. The results suggested that solution surface tension mainly influenced the average diameter of hydrogen bubbles that formed on cathode surfaces during the process. Smaller bubbles lead to both lower current densities on cathodes and smaller crater sizes on coatings.